A Hoard of Coins found in Linlithgowshire - MacDonald, George (Proceedings of the Society of Antiquaries of Scotland, 1922)
An earthenware vessel contained a hoard of coins which had been wrapped in textile. A total of 244 coins comprised Scottish gold and silver with some of English silver.